Proposal of concentration limits for determining the hazard property HP 14 for waste using ecotoxicological tests. (April 2018) - Hennebert, Pierre
Highlights: HP 14 is the most classifying hazard property of waste in the EU. Concentration limits for ecotox tests must be built from the European list of waste. The concentration limits are the highest test results from a panel of non-hazardous waste. Hazardous waste (by list) are classified hazardous by test; the matching is perfect. Abstract: Different ecotoxicological test batteries and concentration limits have been proposed to assess the hazard property (HP) HP 14 'Ecotoxic' for waste in the European Union and its member states. In test batteries, if the concentration of waste in the culture/dilution medium producing 50% of inhibitory biological effect in one or more test(s) is below the concentration limit of the test, the waste is classified as hazardous. A summarized review of the test batteries proposed since 1998 is presented. The last proposed test battery uses seven aquatic and terrestrial species with standardized methods, but with options and uniform concentration limits of 10% of waste eluate or solid waste in the culture/dilution medium. No attempt was made to match this hazard assessment with the classification made in the European List of Waste (LoW). The aim of this paper is to propose for the same test battery (reduced to 6 tests without options) concentration limits that match with the European List of Waste. This list was taken as reference (despite the fact that waste can be hazardous for other properties than the most frequent HP 14, and its partly political nature for some opinions). The concentration limits (CLs) for tests are the concentrations producing the highest ecotoxicological effects for each test observed in a non-hazardous waste set. Data from Germany, France and Belgium (from in total 5 different sources from 2009 to 2016) with the above-mentioned test battery (without options) were gathered for 81 samples, being the largest set ever published. In total, ten non-hazardous (NH) waste samples (as defined by the LoW and for most of them checked by chemical composition) were used to establish CLs. These CLs were then applied to 13 hazardous (H) waste by the LoW, and all were classified as hazardous. The matching of the resulting classification with the LoW is convincing. For the 58 'mirror entries' in the LoW (hazardous or not depending of the presence of hazardous substances), 37 were classified H (64%) and 21 were classified NH (36%). These concentration limits can be refined with the method proposed here, as soon as additional data of NH waste (by list and by composition) are available. The test battery (without options) and the concentration limits (in percent of waste in the culture/dilution medium) proposed are the following: A waste is hazardous for HP 14 'Ecotoxic' if the concentration of waste (eluate or solid) in the culture/dilution medium producing 50% of biological effect relative to the control EC50 -30 min of Vibrio fischeri (EN ISO 11348-3) is lower than 15.8%, or if the EC50 -72 h of Pseudokirchneriella subcapitata (EN ISO 8692) is lower than 7.03%, or if the EC50 -48 h of Daphnia magna (EN ISO 6341) is lower than 7.95%, or if the EC50 -6h of Arthrobacter globiformis (ISO 18187) is lower than 2.25%, or if the EC50 -14d of Brassica rapa (EN ISO 11269-2) is lower than 13.7%, or if the EC50 -48 h of Eisenia fetida avoidance test (ISO 17512-1) is lower than 3.75%. These CLs range between 2% and 16%, which is in line with the typically 10% concentration proposed without validation. To fix regulatory concentration limits, the regulators can use these CLs and the uncertainty of the ecotoxicological tests (standard deviation of inter-laboratory reproducibility typically of 25% of the mean, as published in the standards). Classification of waste for HP 14 with these tests and concentration limits will agree with the European List of Waste.